Radiological characterization of gilthead seabream ( Sparus aurata ) by X‐ray computed tomography - Diana Ceballos‐Francisco; Nuria G. Carrillo; Francisco J. Pardo‐Fernández; Alberto Cuesta; María Á. Esteban (Journal of Fish Biology, 2020)
In recent years, the increasing use of fish as new animal models in scientific research and the growth of fish farming (mainly for human consumption) have highlighted the need for advanced technology to deepen our knowledge of fish biology. Hence, the present study was carried out to radiologically analyse the whole body of gilthead seabream ( Sparus aurata ) specimens using X‐ray computed tomography (CT). Images were acquired in an Albira SPECT/PET/CT tri‐modal preclinical‐scanner. Segmentation, measurements and three‐dimensional reconstruction were made using the Carestream Molecular imaging Albira CT system in conjunction with Pmod, AMIDE and Amira software packages. The results showed that the density values of gilthead seabream are in the range −700 to +2500 HU for the whole body. We also determined the density ranges that topographically coincide with the swim bladder, soft tissues, fat, skin and skeleton. This work describes, validates and demonstrates the application of a fully automated image analysis technique to study and quantify fish body composition, whether segmented or as a whole. In addition, the basis for applying this image technique in other in vivo studies is established.